Shareholder Value Creation in Merger and Acquisition Transactions-The UK Evidence - QIN, Fangzi (2015)
Abstract This study examines the short-term performance of UK acquiring firms for the time period 1994-2003 and finds out the impact of several specific factors on performance. This study firstly reviews the motives and previous empirical studies in merger and acquisition (M&A) transactions and sets up related hypotheses to help investigate performance of acquiring firms and potential influencing factors. Then, as a main research methodology, the standard event study methodology is carried out based on both five-day and three-day event windows. Moreover, cross-sectional regression is also conducted to find which factors have significant impact on performance of acquiring firms. The main finding of this study is that in the short term, M&A transactions create positive but insignificant abnormal returns for shareholders of UK acquiring firms for the time period 1994-2003. Moreover, after taking into account different factors (i.e. payment method, type of target firm, relative size of target, relatedness of acquiring firm and target firm and industry), it reveals that short-term performance of UK acquiring firms is affected by payment method and type of target firm significantly. Furthermore, this study specially proves that industry (i.e. financial industry and non-financial industries) has insignificant impact on performance of UK acquiring firms. Additionally, it also indicates that in this study, the main conclusions drawn by the results from the whole sample including M&A transactions in all industries and by the results from the subsample including M&A transactions in non-financial industries are similar.